Multi-scale modelling and controlled synthesis of Titania nanoparticles - Akindeju, Michael Kehinde (Curtin University, 2013)
Considering the level of current interests in the continuous synthesis of Titania, the Chemical and Manufacturing Industry is expected to benefit from the results of this work which proposed and implemented a tailor-made scheme for the continuous synthesis of Titania nanoparticles to develop a process with improved energy efficiency, predictable particle size, narrower size distribution, polymorph selectivity, and better controllability.This study investigated and modelled six polymorphs of Titania: Rutile, Anatase, Brookite, high-pressure Brookite, the columbite-type TiO2-II and Corundum-like type CLT, under constant pressure using the General Utility Lattice Program (GULP) with satisfactory results when compared to the classical data on the subject. The simulated thermodynamic, mechanical and optical properties compared favourably with known references and were used to simulate stable optimized nanoparticles except for CLT due its large compressibility and electronegativity equalization correction.The simulated properties were used as parameters to model the network reactor system comprising of a spinning disc in the aerosol reacting volume, CSTR in the “sol” volume and settling volume according to the two-step reaction chemistry for precipitating TiO2 in a pilot scale set-up was used to validate the simulated results in Chapter 5. On one hand and using only the dominant process factors, laboratory experiments were conducted to test between 30°C and 100°C with a 10°C step change (but including 47°C being the optimum temperature predicted by simulation) to establish and verify the optimum temperature for the process while varying TiCl4 molar concentration by 0.5 step change between 0.5 and 2M. On the other hand, a pilot scale was used to validate the impact of the CSTR impeller speed on the particle size and distribution varying TiCl4 molar concentration by 0.5 step change between 0.5 and 2M. Further, H2O/TiCl4 was varied with step changes of 2 between 2 and 6.From the numerical results and graphs, two conclusions were drawn that 1. In general and for all three reactor modes of operations, it is evident that the higher the spin and/or impeller speed, the smaller the particle size and the narrower the distribution for the range examined. 2. In contrast, the three modes of operations presented varied results. Whereas the SD-CSTR gave narrower distributions with mostly single peaks, the SD alone and CSTR alone produced multi-peaks and wider size distributions. Both of the above therefore led to an overall conclusion that the SD-CSTR is a more efficient reactor mode for the continuous synthesis of TiO2.In addition to the above, parametric relationship between the modal particles sizes and critical operating conditions was also developed to achieve predictability of modal particle size, narrow size distribution and polymorph selectivity using the molar concentration, reaction temperature, degree of supersaturation and spinning rate as major factors by deploying Darby’s (2001) Newtonian fluid relationship between shear rate and viscosity to obtain an empirical correlation comprising both molecular and reactor specific parameters. A general trend was observed when the empirical relationship was plotted for several operating conditions leading to a quick shortcut equation that can be used upon establishing initial particle size from a cooling precipitation reaction in the laboratory.At completion, and using Rutile as base case, this work successfully investigated and developed a tailor-made process for continuously synthesizing Titania nanoparticles using molecular modelling approach to evaluate the invariable intensive properties which were used to develop models that described the process with the following significant contributions: a) Compared to the Chemical Vapour Deposition (CVD) technology that operates at 900°C – 1100°C, this system operates between 25°C and 100°C depending on target characteristics of the desired nanoparticles. This is a significant saving in energy requirements. b) This system produces particles within controllable and predictable narrow size distribution unlike the wide particle distribution obtainable from using the SD or CSTR alone in the Sol-Gel process. c) While other technologies require very high super-saturation levels, typically in 20 –1000 range, our novel system only requires a maximum of 8; hence preventing material wastages. d) By increasing the degrees of freedom, this system achieves controllability for i. Particle size ii. Particle size distribution iii. Polymorph selectivitye) This system is suitable for the synthesis of temperature sensitive organic nanoparticles because the optimal operating temperature is well below the temperatures required to denature most organic particles. f) This device is suitable for both aqua and non-aqua flow processes; adequate for developing target oriented drug delivery nanoparticles. g) The overall process time for this system is 0.859s compared to the more than 2s for Sol-Gel processes (typically followed by calcination) and more than 5min for CVD. This translates into a gross reduction in the total time required for products to reach the target market.Furthermore, there are indications that hydroxylated TiO2 may present yet unknown but important applications in semiconductors.